World Bank Resilience M&E : Good Practice Case Studies - World Bank Group; Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2017)
These case studies were developed as part of the World Bank's Results Monitoring and Evaluation for Resilience Building Operations (ReM&E) project, which aims to develop and increase the application of systematic, robust, and useful approaches to monitoring and evaluation (M&E) for resilience-building projects/programs within the World Bank. The case studies propose to foster a grounded understanding of good ReM&E practices through real-world examples. The intended audiences are Task Team Leaders (TTLs) and operational staff of the World Bank who design and/or oversee the implementation of M&E for resilience-building operations, as well as their counterparts at other development organizations.